Perancangan Media Promosi SMP IT Dar El Iman dalam Bentuk Audio Visual - Eka Febdianda `Ramadhan (fakultas Desain Koomunikasi visual, 2020)
SMP IT Dar El Iman is a modern school that stands in the center of the city of Padang which was founded in 2015 under the auspices of the Dar El Iman foundation, where SMP IT Dar El Iman has complete facilities and quality graduates. The absence of a promotional video, made the author to appoint Dar El Iman IT Middle School as the title of the Final Project with the title